Appropriateness of hospital admissions in a university hospital in Egypt: Analyzing a preintervention phase - Aya Mostafa Abdellatif; Mahi Mahmoud A L Tehewey; Mervat Hassan Rady; Amany Mokhtar Abdelhafez; Mai Ahmed Eldeeb; Hebat Allah Mohammed Salah Gabal (Wolters Kluwer Medknow Publications, 2022)
Background: Identifying the magnitude of this improper use and applying interventions to eliminate unnecessary hospitalization will reduce health-care expenditure, improve the quality of care for patients, and increase the accessibility to care for actual patients in need on waiting lists. Aim of Work: To measures the rate of inappropriate admissions at the Ain Shams University Hospital. Methods: This research is the preintervention phase of a study conducted to improve the appropriateness of patient admission at this hospital. The appropriateness evaluation protocol (AEP) was used to review the appropriateness of 576 hospital admissions over 100 days. The patients' medical records were stratified according to the admission route into two groups, namely emergency and outpatient admission. Next, the systematic random samples were taken from each stratum based on the admission list of the previous day. Results: The results showed that 20.5% of the sampled cases were inappropriately admitted. Furthermore, a statistically significant difference was observed between appropriately and inappropriately admitted cases regarding gender and shifts during which admission occurred in addition to body systems affected; inappropriate admissions were more among females, and admissions occurred most frequently during the morning shifts (8:00 am-2:00 pm). The remaining other factors that were studied also proved insignificant. Conclusion: It can be concluded that a considerable proportion of hospital admissions is inappropriate, especially in the elective surgery department, and these admissions vary according to patient's gender, shifts during which admission occurred, and the affected body systems. Recommendations: Adopting hospital admission policies based on the AEP criteria in addition to training of physicians on these criteria would help prevent inappropriate admission and ensure optimization during use of hospital facilities.